Development of Creative-Thinking Instrument in Mathematics Problem Solving Based on Logical Mathematics Intelligence - Adnyani, Luh Putu Widya; Kurniawan, Indra; Pinahayu, Ek Ajeng Rahmi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2018)
The aim of this research is knowing whether research instrument is feasible or no to get data of research. The instrument of this research is logical mathematics quotient test with 25 problems in multiple choice and mathematics problem solving test with 4 questions in essay.Â  Testing the appropriateness of instrument of logical mathematics intelligence consist of content validity, level of problem difficulties, power differentiator, and reliability. Meanwhile, testing the appropriateness of instrument of mathematics problem solving use content validity. The validator for both of logical mathematics intelligence test and mathematics problem solving test is expert judgement. There are 39 students of Senior High School as respondent who are joining instrument try out. The results of appropriateness of instrument show: 1) there are 25 questions of logical mathematics quotient instrument which are feasible to take research data, and 2) instrument of mathematics problem solving in linier equation system material is feasible to use with some revisions from expert judgment.